Safe and healthy food in traditional food markets in the WHO European Region (World Health Organization, Regional Office for Europe, 2021)
This technical report contains guidance on the promotion of safe and healthy food in traditional markets within the WHO European Region, targeting all stakeholders from policy-makers to market workers. This document outlines the main guiding principles of a safe and healthy traditional food market and proposes a stepwise approach to the implementation of safe and healthy traditional food market initiatives.
Keywords: Noncommunicable Diseases; zdravá strava; veřejné zdravotnictví; neinfekční nemoci; Food Safety; bezpečnost potravin; Diet, Healthy; nutriční terapie, dietoterapie a výživa